2017
DOI: 10.7554/elife.21629
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dynamics regulating the timing of decision-making in C. elegans

Abstract: Brains regulate behavioral responses with distinct timings. Here we investigate the cellular and molecular mechanisms underlying the timing of decision-making during olfactory navigation in Caenorhabditis elegans. We find that, based on subtle changes in odor concentrations, the animals appear to choose the appropriate migratory direction from multiple trials as a form of behavioral decision-making. Through optophysiological, mathematical and genetic analyses of neural activity under virtual odor gradients, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 80 publications
10
93
0
Order By: Relevance
“…elegans neurons in the presence of odor stimuli resembling those that the worms experience during the odor avoidance behavior in the plates (Fig. 7A) (Tanimoto et al, 2017). Using the OSB2 system, we found that ASH neurons are the major sensory neurons to cause pirouettes upon increases in 2-nonanone concentration (Tanimoto et al, 2017).…”
Section: Responsiveness Of Sensory Neurons To Odor Increase Was Modulmentioning
confidence: 90%
See 4 more Smart Citations
“…elegans neurons in the presence of odor stimuli resembling those that the worms experience during the odor avoidance behavior in the plates (Fig. 7A) (Tanimoto et al, 2017). Using the OSB2 system, we found that ASH neurons are the major sensory neurons to cause pirouettes upon increases in 2-nonanone concentration (Tanimoto et al, 2017).…”
Section: Responsiveness Of Sensory Neurons To Odor Increase Was Modulmentioning
confidence: 90%
“…6D and E). Because the previous study demonstrated that worm odor avoidance behavior depends on dC rather than C at least in the naive condition (Tanimoto et al, 2017), one possibility is that the changes in the responsiveness of worms to dC is the underlying reason for the enhanced odor avoidance. However, it is also possible that the odor-experienced worms were somehow located farther away from the odor source than the unexperienced worms, and hence, sensed lower odor concentrations and shallower odor concentration change than the latter.…”
Section: Comprehensive Extraction Of Behavioral Features Modulated Bymentioning
confidence: 97%
See 3 more Smart Citations